Effects of Al:Si and (Al + Na):Si ratios on the properties of the international simple glass, part I: Physical properties. Issue 1 (26th September 2020) - Reiser, Joelle T.; Lu, Xiaonan; Parruzot, Benjamin; Liu, Hongshen; Subramani, Tamilarasan; Kaya, Huseyin; Kissinger, Ryan M.; Crum, Jarrod V.; Ryan, Joseph V.; Navrotsky, Alexandra; Kim, Seong H.; Vienna, John D.
Abstract: Understanding composition‐structure‐property relationships of high‐alumina nuclear waste glasses are important for vitrification of nuclear waste at the Hanford Site. Two series of glasses were designed, one with varying Al:Si ratios and the other with (Al + Na):Si ratios based on the international simple glass (ISG, a simplified nuclear waste model glass), with Al2 O3 ranging from 0 to 23 mol% (0 to 32 wt%). The glasses were synthesized and characterized using electron probe microanalysis, X‐ray photoelectron spectroscopy, small angle X‐ray scattering, high‐temperature oxide melt solution calorimetry, and infrared spectroscopy. Glasses were crystal free, and the lowest Na2 O and Al2 O3 glass formed an immiscible glass phase. Evolution of various properties—glass‐transition temperature, percentage of 4‐coordinated B, enthalpy of glass formation—and infrared spectroscopy results indicate that structural effects differ based on the glass series.